Photosensitive injectable systems for biomedical applications - Skrobot, J.; Fray, M. el (Polimery, 2010)
The paper is a review of photosensitive injectable (i.e. introduced by low-invasion surgery methods into the places subjected to therapy) polymer compositions for medical applications. The article contains a short introduction into the field of stimuli-responsive biomaterials and presents the characteristics of main groups of polymers which structures allowing formation of photo-cured compositions (synthetic and natural polymeric hydrogels, polyanhydrides, polyesters or polyurethanes). The methods of modifications of such compounds are given as well as the examples of photosensitive materials applications in medicine. The existing problems and limitations are also mentioned.